2012
DOI: 10.5194/acp-12-10797-2012
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization and fragmentation during ambient organic aerosol aging: application of the 2-D volatility basis set to field studies

Abstract: Abstract. Multigenerational oxidation chemistry of atmospheric organic compounds and its effects on aerosol loadings and chemical composition is investigated by implementing the Two-Dimensional Volatility Basis Set (2-D-VBS) in a Lagrangian host chemical transport model. Three model formulations were chosen to explore the complex interactions between functionalization and fragmentation processes during gas-phase oxidation of organic compounds by the hydroxyl radical. The base case model employs a conservative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(117 citation statements)
references
References 80 publications
(118 reference statements)
2
112
0
Order By: Relevance
“…Hodzic et al (2010) showed that the addition of 40 % oxygen in mass and the drop of two orders of magnitude in volatility upon each oxidation step are found to improve oxygen to carbon atomic ratio predictions, though lead to unrealistically high SOA production. Nevertheless, a number of complex and more realistic schemes has been recently tested and showed that a one-volatility bin shift scheme resulted in the best agreement with the observations (Murphy et al, 2012).…”
Section: Oltmentioning
confidence: 55%
See 1 more Smart Citation
“…Hodzic et al (2010) showed that the addition of 40 % oxygen in mass and the drop of two orders of magnitude in volatility upon each oxidation step are found to improve oxygen to carbon atomic ratio predictions, though lead to unrealistically high SOA production. Nevertheless, a number of complex and more realistic schemes has been recently tested and showed that a one-volatility bin shift scheme resulted in the best agreement with the observations (Murphy et al, 2012).…”
Section: Oltmentioning
confidence: 55%
“…To cope with this deficiency, a two-dimensional VBS scheme is developed, which uses the degree of oxidation as a second coordinate ). However, when tested against measurements in Europe it was found that the simple one-dimensional scheme had as good a performance as any of the more complex two dimensional VBS schemes probably due to uncertainties in our understanding of SOA evolution in the atmosphere (Murphy et al, 2012).…”
Section: Oltmentioning
confidence: 99%
“…This may result in an overestimation of OA at long aging timescales up to thousands of kilometers downwind of the source regions. However, this overestimation can be partially offset by the conservative aging scheme used in ORACLE 2-D compared to the relatively aggressive functionalization scheme proposed by Murphy et al (2012). The same addition of oxygen atoms (one or two) is assumed for bSOA-v (SOA from the oxidation of biogenic VOCs); however, its volatility remains unchanged due to a balancing of fragmentation and functionalization effects (Murphy et al, 2012) (Fig.…”
Section: New Photochemical Aging Schemementioning
confidence: 99%
“…Recent studies have suggested that the main difference between these two OOA types is often not so much their volatility, but mostly their oxygen content (Kostenidou et al, 2015;Louvaris et al, 2017). These two OOA types represent distinct oxidation states with O : C of 0.33-0.67 for SVOOA and 0.67-1.00 for LVOOA (Donahue et al, 2012). Therefore, SVOOA can be compared at least as a zero-order approximation against the simulated fresh SOA (Table 3) and LVOOA against the simulated aged SOA (Table 4).…”
Section: Organic Aerosol Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation